524 Effectiveness of Burns Wound Cleansing by Comparison of Prewash and Post Wash Swab Reports. (12th October 2021) - Sayed, M A; Jabeen, S; Soueid, A
Abstract: Aim: The main aim and objective were to optimise wound healing through infection prevention. This clinical audit aimed to investigate the effectiveness of burn wound cleansing in decreasing bacterial load by comparing pre-wash and post-wash swab results against local burn wound management and aseptic non touch technique (ANTT) guidelines. Method: The audit was conducted retrospectively on children admitted to Burns Unit during August 2019, excluding resuscitation burn patients. Pre- and post-wash swabs taken on admission were included and the results obtained from Chameleon database. Data were collected on excel spread sheets including demographic variables such as age, sex, type of injury, percentage total body surface area (TBSA) and mechanism of injury. Data were analysed and results compiled. Results: Fifty patients were admitted over a month period; amongst those 60% were male and 40% female of ages ranging from 5 months to 14 years. Scald (50%) was found to be the most common mode of injury followed by contact burn (36%) involving 0.30 to 9% TBSA. Among 50 patients, 30 (60%) showed no growth in pre-wash and 36 (72%) in post-wash swabs. However, 6% post-wash swabs that were initially negative later showed bacillus cereus, staph aureus, Enterobacter, and Acinetobacter. Similarly, another 4% post-wash swabs developed new microorganisms as compared to pre-wash swabs. Conclusions: The most common bacteria colonising both pre- and post-wash swabs was staph aureus. Overall, cleansing had reduced the bacterial load significantly around 82% very effective. It is imperative to stick to local guidelines to reduce morbidity and mortality in burn patients.